Strawvenger / Syazarisya Hud - Hud, Syazarisya (2021)
Social media portfolio (Facebook) is the report about individual project of subject Principles of Entrepreneurship (ENT530). This project require student to register their business at https://lms.go-ecommerce.my/ for Malaysia Digital Economy Corporation (MDEC) to get into their business activities. In addition, they also require to create Facebook page for them start their business Business activities that student need to do based on this project is they have to do few tasks and one of it is posting a teaser. Teaser is a form of advertising tactic in which the advertiser teases and gives a sneak peek of the product that the buyer is about to purchase. Other than that, they also need to post hard sell, soft sell and graphics for online marketing on their Facebook page. This project takes a time to complete. This report includes an overview of the company, an organisational structure, three (3) different types of Facebook posts (teaser, hard sell, and soft sell), and a conclusion. Essentially, this report is a recap of a student project and the strategy that they used to complete it. The method employed is really interesting and encourages students to think about how to finish it.